Association of genetic variation in IKZF1, ARID5B, CDKN2A, and CEBPE with the risk of acute lymphoblastic leukemia in Tunisian children and their contribution to racial differences in leukemia incidence. (2nd April 2016) - Gharbi, Hanene; Ben Hassine, Islem; Soltani, Ismail; Safra, Ines; Ouerhani, Slah; Bel Haj Othmen, Hind; Teber, Mouheb; Farah, Ahlem; Amouri, Hassiba; Toumi, Nourel Houda; Abdennebi, Salima; Abbes, Salem; et al.
ABSTRACT: Recent genome-wide association studies (GWAS) focusing on pediatric acute lymphoblastic leukemia (ALL), the most common malignancy in children younger than 15 years old, have found evidence that single-nucleotide polymorphisms (SNPs) in IKZF1 (7p12.2), ARID5B (10q21.2), CDKN2A (9p21.3), and CEBPE (14q11.2) are strongly associated to the risk of developing pediatric ALL. These studies have been conducted in European and Thai populations, and it is unclear whether these observations generalize to other populations with a lower incidence of pediatric ALL. In order to explore the impact of these variants on pediatric ALL risk in the Tunisian population, we genotyped 58 cases of pediatric ALL and 150 controls for SNPs rs4132601 (7p12.2), rs7089424 (10q21.2), rs3731217 (9p21.3), and rs2239633 (14q11.2). Our results, which are consistent with findings in European populations, show that 3 SNPs, i.e., rs4132601 ( P = .00116, odds ratio [OR] = 2.78, 95% confidence interval [CI] = [1.42, 5.87]), rs7089424 ( P = .0022, OR = 0.49, 95% CI = [0.31, 0.79]), and rs2239633 ( P = .0010, OR = 0.47, 95% CI = [0.29, 0.75]) are significantly associated with a higher risk of developing pediatric ALL ( P < .05). Furthermore, we show differences in allele frequencies in SNPs between Tunisian and Caucasian and/or Thai populations (e.g., CEBPE, rs2239633; population attributable risk [PAR] ∼15-fold the PAR of Thai population). These differences, combined with differences in linkage disequilibrium structure between populations and differences in size between populations, may contribute to racial differences in pediatric ALL incidence.